Twinkle Lighting Sdn Bhd - Tabari, Elvy Brenda; Benson, Helina; Refley, Evylona; Kirinus, Sheronna; Bianus, Quayra Kennaelyea (2014)
Twinkle Lighting Sdn Bhd are form to offers a wide range of well-designed light products at prices so low that as many people as possible will be able to afford them. We are offers the shopping product, product items, product line and mix of lamp or lighting. Our company's mission is our product will become the first choice in Sabah and to develop creative lighting products which provide better light, visual comfort and unique experiences to users. With this mission, we come with a goal that will be strives to be good supply of high quality of lighting whilst being affordable for everyone. Twinkle Lighting Sdn Bhd applying the selling concept in our business by doing advertisement to approach and attract our customer. By this product, we are focus into geographic segmentation and demographic segmentation only.